The Greek Crisis and Financial Assistance Programmes: An Evaluation - Michael G. Arghyrou (Center for Economic Studies and ifo Institute (CESifo), 2015)
We analyse the background of the Greek debt crisis and evaluate the three Greek financial assistance programme. The crisis and the first programme's (2010-11) failure were mainly the result of misguided internal policies. The second programme (2012-14) achieved progress towards recovery but this was fragile and was cancelled out by Greece's stand-off with her lenders in the first half of 2015. The stand-off was one that predictably Greece could not win, due to the lack of a credible growth plan; and the adoption of a transparently non-credible ultimatum-game strategy. These explain the signing of the third programme in August 2015.
Keywords: E00; F40; 330; Greece; euro; crisis; financial assistance programmes